The Preferences of Interior Design of the Middle-Class Families in Jordan - Sinan, Wafa Moh’d Fawaz; Eryildiz, Demet Irkli (Journal of engineering sciences and information technology, 2023)
The research aims to study preferences in middle-class homes in Jordan and the impact of these preferences on the psychological state of the resident inside the home. Find out the reasons why Jordanians choose their homes, including furniture, materials, colors, accessories, and more. The research also aims to analyze the residents' choices to reach results that enhance the residents' comfort in their homes and their sense of belonging to this space. The research also aims to know the foundations on which the interior spaces of homes are designed, such as living rooms, bathrooms, kitchens, bedrooms, storage rooms, and balconies, with a focus on other aspects of design factors: residents' reactions, feelings, memories, attachment to place, and interests. In addition, the research focuses on the exploratory and descriptive aspects of interior design in a real-life context, and provides comprehensive information that is extracted and released in an integrated manner for home design in Jordan, and in a reliable manner. for residents.The methodology of this study will depend on the systematic review of the literature, the analysis of the narrative style of secondary data, the qualitative subjective approach, and also in the philosophy of positivity or positivism, which is an approach to the study of society by observing people, social life, experiences and statistics that reveal the reality of society. Where the purpose of this study will be to influence social changes and improve human conditions in general by studying the influence of psychology and human study on the design of the middle class house in Jordan.The results of the study showed that several main factors affect the choices of homes by Jordanians in terms of interior design options, the most important of which is the economic factor, as this research is concerned with the middle class in Jordanian society, financial ability and height. Prices affect the design of homes in Jordan, as most of the homes that were studied did not hire an interior designer because of their cost, which prompted them to choose the elements of the house on their own, without any interdependence or continuity in furnishing the spaces. And the choice of colors and materials, which made homes have many design problems and created uncomfortable spaces for people to spend a long time in.
Keywords: Inhabitant behavior; interior design; middle class houses; Residents' preferences